2012
DOI: 10.1186/2047-2382-1-3
|View full text |Cite
|
Sign up to set email alerts
|

What are the effects of wooded riparian zones on stream temperature?

Abstract: Background: Predicted increases in stream temperature due to climate change will have a number of direct and indirect impacts on stream biota. A potential intervention for mitigating stream temperature rise is the use of wooded riparian zones to increase shade and reduce direct warming through solar radiation. To assess the effectiveness of this intervention, we conducted a systematic review of the available evidence for the effects of wooded riparian zones on stream temperature. Methods: We searched literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 49 publications
4
40
0
3
Order By: Relevance
“…The unshaded areas showed up to 2.6°C higher daily WT max in the extreme heatwave days (KĂŸ) than fully or patchy shaded ones (VSI 6000 above 0.4) in the processed area did. This is consistent with Bowler et al (2012) who concluded that mean WT max are up to 4.9°C lower at forested riversides than at pasture riversides.…”
Section: Water Temperature Variationssupporting
confidence: 81%
See 1 more Smart Citation
“…The unshaded areas showed up to 2.6°C higher daily WT max in the extreme heatwave days (KĂŸ) than fully or patchy shaded ones (VSI 6000 above 0.4) in the processed area did. This is consistent with Bowler et al (2012) who concluded that mean WT max are up to 4.9°C lower at forested riversides than at pasture riversides.…”
Section: Water Temperature Variationssupporting
confidence: 81%
“…However, WT max and WT range had peaks at unshaded reaches, of up to approximately 4°C difference to shaded ones, which followed a steadily increasing curve. These findings correlates well with the findings of Bowler et al (2012), Johnson (2004) and Webb et al (2008) which show that if a riverine reach is fully clear cut, the daily WT max and WT range are particularly affected.…”
Section: Vsi and Its Spatial Scale In Terms Of Water Temperaturesupporting
confidence: 79%
“…The warm water temperatures in this stream are probably related to changes in the riparian vegetation that allowed more sunlight to reach the stream channel. Bowler et al (2012), working in European streams, observed that water temperatures were positively correlated with light input.…”
Section: Discussionmentioning
confidence: 99%
“…Canopy removal eliminated the shading effect of the trees naturally implying a change in lighting conditions in the open stretches of the impact stream following clearfelling. Solar radiation is the predominant contributor of energy for summer warming in streams with no canopy (Bowler, 2012). Gomi et al (2006) suggest riparian areas along streams protect the stream from increased thermal variability, with effects varying to some degree with buffer width.…”
Section: Discussionmentioning
confidence: 99%